(untitled) (Contemporary Mathematics, 2023)
The objective of this paper is to estimate the best possible upper bound to the third Hankel determinant for the inverse of functions with normalized conditions f (0) = 0, f ′(0) = 1 in the unit disc whose derivative has positive real part.